Pemanfaatan Kahoot dan Quizizz Sebagai Alat Media Pembelajaran Interaktif untuk Meningkatkan Kualitas Belajar di SMAN 1 Parittiga - Fithriawan Nugroho; Aditya Ahmad Fauzi; Faishal Farras; Muhammad Iqbal Hanafi; Siti Kamilah; Marna Marna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The use of technology in education has become an essential need in modern learning. This study aims to analyze the utilization of Kahoot and Quizizz as interactive learning tools to enhance student learning quality at SMAN 1 Parittiga. The research employs a qualitative approach with observation and interview techniques to explore student and teacher experiences in using these platforms. The findings indicate that Kahoot and Quizizz significantly improve students' motivation, engagement, and comprehension of learning materials. Kahoot is more effective in creating a competitive learning atmosphere, while Quizizz provides flexibility for students to learn at their own pace. However, some challenges arise, such as reliance on a stable internet connection and the need for teacher training to optimize platform features. Therefore, it is recommended that schools improve digital infrastructure and provide training for teachers to support the optimal implementation of technology-based learning.